Phase Separation in a Novel Selective Lithium Extraction from Citrate Media with D2EHPA - Tiaan Punt; Steven M. Bradshaw; Petrie Van Wyk; Guven Akdogan (Metals, 2022)
Lithium-ion battery (LIB) recycling has received continued interest in recent years due to its benefits, which include reducing the environmental impact of spent LIBs and providing a secondary source of valuable metals, such as Li, Co, and Ni. This paper characterized the Li separation with D2EHPA from citrate media as a function of pH and identified the optimal overall Li separation at a pH of 5.5. The Li separation was optimized at a pH of 5.5, with which it was concluded that 23 vol.% D2EHPA and an O/A ratio of 4 provided the best Li separation, for which 66.1% Li was extracted with 26.9% residual Mn, 6.8% Co, and 7.7% Ni in a single stage. The formation of a reversible hydrophobic third phase was identified during Li extraction at a pH of 5.5 or greater. Investigation of the third phase revealed that more than 99% of the Li, Co, and Ni were extracted to the third phase, while more than 69% of the Mn was extracted to the organic phase. STEM images of the third phase revealed a honeycomb-like structure, which was hypothesized to be a 2D mesoporous film caused by the insolubility of the organometallic complexes in the aqueous and organic phase.